Genotypic difference of garlic (Allium sativum L.) cultivars for growth, bulb yield and yield related attributes at Tigray Province, Northern Ethiopia - Biratu, W.; Molla , B.; Abebe , H.; Gebremeskel , H. (International Journal of Horticultural Science, 2023)
The experiment was conducted at Ofla district from June to October of 2017 and 2018 cropping season to select high yielding and adaptable garlic cultivar(s). Six garlic cultivars namely Chefe, Tsedey, Holeta local, Kuriftu and Bora-4 and one Ofla Local were evaluated. The experiment was arranged in completely randomized block design (RCBD) with three replications. Different growth, phenology, yield and yield related data were collected. Leaf length, leaf width, bulb diameter and length were significantly (p<0.05) influenced by garlic cultivars in both cropping seasons. Bulb weight and number of cloves per bulb were highly significantly (P<0.01) influenced by cultivars in both cropping seasons. Also, marketable yield, unmarketable yield and total yield ha-1 were highly significantly (P<0.01) influenced by cultivars in both seasons. During 2017 and 2018, the highest marketable bulb yield was observed from Ofla Local cultivar with an average value of (8.86 t/ha) and (9.06 t/ha) respectively. During the 2017 cropping year, the maximum and significantly higher total bulb yield of 10.21 t/ha was recorded on the Ofla Local cultivar. Moreover, in 2018, this cultivar provided the maximum total bulb yield of 9.80 t/ha. Therefore, the Ofla Local cultivar showed the greatest performance for growth, yield and yield related attributes. Thus, it is recommended for cultivation in areas having similar agro-ecology. To improve the productivity of garlic, it is important to study and identify the optimum fertilizer level and spacing in the study area.